Preparation method of aerogel block material and aerogel prepared by same
Carbon/silica aerogel block material was prepared by compounding activated cyanobacteria powder with hydrophobic modified silica hydrosol, and undergoing aging, freeze-drying and high-temperature carbonization, and silica gas was solved The problem of insufficient mechanical strength and thermal stability of the gel has achieved significant improvement in material performance and the reuse of cyanobacteria.
Patent Information
- Application Number
- CN202411616964.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
The existing silica aerogels have poor mechanical strength, high brittleness, insufficient water resistance and thermal stability, and their performance is degraded especially at high temperatures. At the same time, the selection of carbon precursors failed to fully consider factors such as the availability of raw materials and environmental protection.
Carbon/silica aerogel block material was prepared by dispersing activated cyanobacterial powder into hydrophobically modified silica watersol, and aging, freeze-drying and high-temperature carbonization.
It improves the mechanical strength and thermal stability of silica aerogel, enhances its performance under high temperature conditions, and at the same time realizes effective treatment and reuse of cyanobacteria.
Smart Images

Figure CN119461390A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aerogels, and in particular to a method for preparing an aerogel block material and an aerogel prepared therefrom. Background Art
[0002] Silica aerogel is a gel material with a three-dimensional network structure formed by the accumulation of silica colloidal particles. It has the properties of large specific surface area, high porosity, low density and low thermal conductivity. At present, SiO2 aerogel is widely used in thermal insulation, sound insulation, noise reduction, adsorption and other aspects.
[0003] Compared with traditional materials, porous carbon materials have superior properties such as low cost, good chemical stability, environmental protection, good electrical and thermal conductivity, high mechanical strength, low density, and diverse morphology. At the same time, the pore structure can be adjusted through different synthesis methods, and the raw materials are easily available, and porous carbon materials can be obtained from a variety of precursors. Cyanobacteria, as the main pollutant of water bodies, exist in large quantities in rivers, lakes and seas in my country. The treatment and reuse of cyanobacteria are of great significance. Cyanobacteria contain a large amount of protein, amino acids and polysaccharides. The presence of amino, hydroxyl and carboxyl active groups in the molecules enables them to have good compatibility with inorganic materials.
[0004] However, in the process of actual application, researchers found that the mechanical strength of silica aerogel is poor due to the weak interaction between particles inside it. On a macro scale, it exhibits disadvantages such as greater brittleness, easy breakage, poor toughness and poor water resistance. Especially at high temperatures, the silica aerogel will experience pore collapse and structural damage, which will lead to a decrease in its performance.
[0005] The existing one- and two-dimensional biocarbon synergistically enhanced carbon aerogel material and its preparation method and application, as disclosed in Chinese patent application number (CN114380285A), firstly treat the one- and two-dimensional biocarbon-based precursors for use; then mix the glucose solution and molten paraffin and emulsify to obtain an oil-in-water emulsion, add the one- and two-dimensional biocarbon-based precursors, acrylamide, methylenebisacrylamide and ammonium persulfate, and obtain the carbon aerogel material precursor at 300-600°C after freeze-drying; finally, mix the carbon aerogel material precursor and potassium hydroxide solution and evaporate to dryness, and then carbonize it at a high temperature of 700-900°C to obtain the one- and two-dimensional biocarbon-enhanced carbon aerogel material. Although it is possible to prepare aerogel materials by using biochar such as sycamore fluff, cotton wool and ground peanut shells as carbon precursors, the selection of carbon precursors does not take into account the availability of raw materials, the benefits of using raw materials for environmental protection, the difficulty of compounding, mechanical strength, thermal stability and other aspects, resulting in the inability to rationally select carbon precursor raw materials for preparing aerogel materials. Summary of the invention
[0006] In view of the shortcomings of the prior art described above, the purpose of the present invention is to provide a method for preparing an aerogel block material and an aerogel prepared therefrom, so as to solve the problems in the prior art that the mechanical strength of silica aerogel is poor due to the weak interaction force between the internal particles of silica aerogel, and the aerogel exhibits the disadvantages of being relatively brittle, easy to break, poor toughness and poor water resistance on a macro scale. Especially under high temperature conditions, the silica aerogel will experience pore collapse and its structure will be destroyed, thereby causing its performance to deteriorate. Moreover, in the selection of carbon precursors, the availability of raw materials, the benefits of the use of raw materials for environmental protection, the difficulty of compounding, mechanical strength, thermal stability and other aspects are not taken into consideration at the same time, resulting in the problem that the carbon precursor raw materials for preparing aerogel materials cannot be rationally selected.
[0007] To achieve the above-mentioned object and other related objects, the present invention provides a method for preparing an aerogel block material, comprising the following steps: dispersing activated cyanobacteria powder into a hydrophobically modified silica hydrosol to obtain a silica hydrogel; subjecting the silica hydrogel to aging and freeze-drying treatments in sequence to obtain a cyanobacteria-containing silica aerogel composite material; and carbonizing the cyanobacteria-containing silica aerogel composite material at a high temperature in an inert gas using the cyanobacteria as a carbon precursor to obtain a carbon / silicon dioxide aerogel block material.
[0008] In one embodiment of the present invention, before dispersing the activated cyanobacteria powder into the hydrophobically modified silica hydrosol to obtain the silica hydrogel, the process includes: adding the cyanobacteria powder into an activator solution, placing the solution in an oscillator, and oscillating the solution at room temperature for activation; after the activation is completed, centrifuging the solution and washing the solution to neutrality, and then placing the solution in a 100° C. oven for vacuum drying to obtain the activated cyanobacteria powder.
[0009] In one embodiment of the present invention, the activator solution includes an activator and water, the concentration of the activator solution is 10wt%~30wt%, and the mass ratio of the cyanobacteria powder to the activator in the activator solution is 1:(1~5).
[0010] In one embodiment of the present invention, before dispersing the activated cyanobacteria powder into the silica sol modified by the organosilane modifier, the method further includes: adding the silicon source and the organosilane modifier to a mixed solution of ethanol and water at room temperature for mixing; after mixing, adding hydrochloric acid to adjust the pH value to acidic, and after a period of hydrolysis reaction, obtaining the silica hydrosol.
[0011] In one embodiment of the present invention, the mass ratio of the silicon source to the organosilane modifier is 1:(0.5-7), the volume ratio of ethanol to water is 1:(0.5-3), the concentration of hydrochloric acid is 0.1 mol / L, the hydrolysis reaction time is 0.5-2 h, and the pH value corresponding to acidity is adjusted to between 2.0 and 3.0.
[0012] In one embodiment of the present invention, the activated cyanobacteria powder is dispersed in a silica hydrosol modified to be hydrophobic to obtain a silica hydrogel, comprising: adding the activated cyanobacteria powder to the silica hydrosol, adding ammonia water after ultrasonic dispersion treatment, adjusting the pH value to alkaline, and obtaining the silica hydrogel.
[0013] In one embodiment of the present invention, the mass volume ratio of the activated cyanobacteria powder and the silica hydrosol is 1: (20-80), the ultrasonic decomposition time is 15-30 min, the concentration of ammonia water is 0.5 mol / L, and the pH value corresponding to alkalinity is adjusted to between 9.0 and 10.0.
[0014] In one embodiment of the present invention, a silica hydrogel is subjected to aging and freeze-drying treatments in sequence to obtain a silica aerogel composite material containing cyanobacteria, including: aging the silica hydrogel to obtain a silica wet gel; soaking and washing the silica wet gel in water at room temperature until it becomes neutral; placing the neutral silica wet gel in a silica gel mold, freeze-drying, low-temperature freezing, and then vacuum drying to obtain a silica aerogel composite material containing cyanobacteria.
[0015] In one embodiment of the present invention, during the aging process, the aging time is 12h~36h, and the aging temperature is 30℃~60℃; during the low-temperature freeze-drying process, the freezing temperature is less than -40℃, and the freezing time is 24h~36h; the vacuum pressure is less than 5Pa; the high-temperature carbonization process includes: heating from room temperature to 350℃; maintaining a constant temperature at 350℃ for 3h; heating from 350℃ to 600℃~800℃; maintaining a constant temperature at 600℃~800℃ for 4h; wherein, the heating rates from room temperature to 350℃ and from 350℃ to 600℃~800℃ are 2℃ / min.
[0016] The present invention also provides an aerogel prepared by the above-mentioned preparation method.
[0017] As described above, the preparation method of an aerogel block material of the present invention and the aerogel prepared therefrom have the following beneficial effects: the activated cyanobacteria powder is dispersed in the hydrophobically modified silica sol by ultrasonic dispersion method. Since cyanobacteria contain a large amount of protein, amino acid and polysaccharide, and the presence of amino, hydroxyl and carboxyl active groups in its molecules can improve the compatibility between cyanobacteria and silica sol, improve the interaction between cyanobacteria powder as a carbon precursor and silica colloidal particles, and through the activation of cyanobacteria powder, the specific surface area of cyanobacteria-based carbon materials can be effectively increased, so that the cyanobacteria-based carbon materials have a rich porous structure. Further, through aging, freeze drying and carbonization processes, a carbon / silica aerogel block material is finally obtained. The fibrous structure of cyanobacteria can be used to effectively improve the mechanical strength of silica aerogel after carbonization, and at the same time improve the thermal stability of silica aerogel under high temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Shown is a schematic diagram of the macroscopic optical structure of the carbon / silicon dioxide aerogel block obtained in Example 1 provided by the present invention.
[0019] Figure 2 Shown is a schematic diagram of the microscopic morphology of the carbon / silicon dioxide aerogel block obtained in Example 1 provided by the present invention.
[0020] Figure 3 Shown are XRD (X-ray diffraction analysis) diffraction patterns of the carbon / silicon dioxide aerogel blocks obtained in Examples 1 to 5 provided by the present invention.
[0021] Figure 4 The table shows the performance parameters of the carbon / silicon dioxide aerogel blocks obtained in Examples 1 to 5 provided by the present invention.
[0022] Figure 5 The figure shows a comparison of the mechanical properties of the carbon / silicon dioxide aerogel and the silicon dioxide aerogel obtained in Example 1 and the comparative example provided by the present invention.
[0023] Figure 6 Shown is an infrared thermal imaging image of the carbon / silicon dioxide aerogel block obtained in Example 1 provided by the present invention. DETAILED DESCRIPTION
[0024] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.
[0025] See also Figures 1 to 6 . It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings in this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions for the implementation of the present invention, so they have no substantial technical significance. Any modification of the structure, change in the proportional relationship, or adjustment of the size should still fall within the scope of the technical content disclosed by the present invention without affecting the effects and purposes that can be achieved by the present invention. At the same time, the terms such as "upper", "lower", "left", "right", "middle" and "one" quoted in this specification are only for the convenience of description, and are not used to limit the scope of the implementation of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the implementation of the present invention without substantially changing the technical content.
[0026] In one embodiment of the present invention, the present invention provides a method for preparing an aerogel block material, comprising the following steps: Step S10: dispersing the activated cyanobacteria powder into the hydrophobically modified silica hydrosol to obtain the silica hydrogel.
[0027] Step S20: subjecting the silica hydrogel to aging, washing and freeze-drying treatments in sequence to obtain a silica aerogel composite material containing cyanobacteria.
[0028] Step S30: carbonizing the cyanobacteria-containing silica aerogel composite material at high temperature in an inert gas using the cyanobacteria as a carbon precursor to obtain a carbon / silicon dioxide aerogel block material.
[0029] In this embodiment, the process of preparing the aerogel block material includes the preparation of silica hydrogel, the preparation of silica aerogel composite material, and the preparation of carbon / silicon dioxide aerogel block material.
[0030] Through step S10: dispersing the activated cyanobacteria powder into the hydrophobically modified silica hydrosol to obtain the silica hydrogel, it can be seen that in the preparation process of the silica hydrogel, the cyanobacteria powder can be used as a carbon precursor to be compounded with the inorganic material, i.e., the silica aqueous solution. Because cyanobacteria contain a large amount of protein, amino acid and polysaccharide, the presence of amino, hydroxyl and carboxyl active groups in the molecule enables the cyanobacteria powder to have good compatibility with silica, so that the cyanobacteria powder is easier to be compounded with silica, thereby improving the compounding effect. Moreover, cyanobacteria exist in rivers, lakes and seas as the main pollutants of water bodies. Through the above method, the effective treatment and reuse of cyanobacteria can be achieved. In this embodiment, the cyanobacteria powder is cyanobacteria powder after activation treatment before being combined with silica, which can effectively increase the specific surface area of cyanobacteria-based carbon materials, so that the cyanobacteria powder has a rich porous structure. Before combining with the cyanobacteria powder, the silica is also modified to convert the hydrophilic silica into a hydrophobic surface structure.
[0031] Through step S20: the silica hydrogel is subjected to aging, washing and freeze-drying treatment in sequence to obtain a silica aerogel composite material containing cyanobacteria. It can be seen that when the silica hydrogel is obtained and the silica aerogel composite material is further prepared, the reliability and stability of the product can be improved by aging the silica hydrogel. The freeze-drying treatment can effectively remove the moisture in the product to maximize the original properties of the silica aerogel composite material containing cyanobacteria, such as the properties of cyanobacteria as a carbon precursor.
[0032] Through step S30: the cyanobacteria-containing silica aerogel composite material is carbonized at high temperature in an inert gas using cyanobacteria as a carbon precursor to obtain a carbon / silicon dioxide aerogel block material. It can be seen that after aging and freeze-drying treatments, the obtained cyanobacteria-containing silica aerogel composite material is carbonized at high temperature, so that the cyanobacteria with a natural fibrous structure are combined with silica particles. After high-temperature carbonization, the cyanobacteria-based carbon fibers are interspersed in the three-dimensional network of the silica aerogel. This structure is beneficial to improving the mechanical strength of the silica aerogel block material, while improving the thermal stability of the silica aerogel block material.
[0033] In one embodiment of the present invention, the cyanobacteria powder needs to be activated before step S10. Specifically, before dispersing the activated cyanobacteria powder into the hydrophobically modified silica hydrosol to obtain the silica hydrogel, the process includes: adding the cyanobacteria powder into the activator solution, placing it in an oscillator, and oscillating it at room temperature for activation; after the activation is completed, centrifuging and washing it to neutrality, and then placing it in a 100°C oven for vacuum drying to obtain the activated cyanobacteria powder.
[0034] In this embodiment, during the activation treatment, the species number of the blue algae used may be FACHB-82. When the blue algae powder is added to the activator solution, the activator used may be at least one of KOH and NaOH.
[0035] In a preferred embodiment provided by the present invention, by using KOH and NaOH as activating agents to activate cyanobacteria powder, the specific surface area of the cyanobacteria-based carbon material can be effectively increased after chemical reaction, so that the cyanobacteria-based carbon material has a richer porous structure.
[0036] Preferably, when the blue algae powder is added to the activator solution, the activator solution includes an activator and water, the concentration of the activator solution is 10wt% to 30wt%, and the mass ratio of the blue algae powder to the activator in the activator solution is 1:(1 to 5). Specifically, the activator can be at least one of KOH and NaOH.
[0037] In one embodiment of the present invention, the silica sol needs to be modified before step S10. Specifically, before dispersing the activated cyanobacteria powder into the silica sol modified by the organosilane modifier, the method further includes: adding the silicon source and the organosilane modifier to a mixed solution of ethanol and water at room temperature for mixing; after mixing, adding hydrochloric acid to adjust the pH value to acidic, and after a period of hydrolysis reaction, obtaining the silica hydrosol.
[0038] In the present embodiment, when the silica sol is modified, the silicon source and the organosilane modifier can be added to a mixed solution of ethanol and water at room temperature in different mass fractions. And after the silicon source, the organosilane modifier, the ethanol and the water are mixed, the pH value is adjusted by adding hydrochloric acid, for example, the pH value is adjusted to between 2.0 and 3.0, so that it is acidic. And after a period of hydrolysis reaction, a silica aqueous solution is obtained. By adding the organosilane modifier, the different hydrophobic functional groups it has can be adjusted to the surface hydrophilicity and hydrophobicity of the silica aerogel finally obtained, so that the hydrophilic silica aerogel is converted into a hydrophobic surface structure, and then the water resistance of the silica aerogel can be further improved.
[0039] Preferably, the mass ratio of the silicon source to the organosilane modifier is 1:(0.5-7), the volume ratio of ethanol to water is 1:(0.5-3), the hydrochloric acid concentration is 0.1 mol / L, the hydrolysis reaction time is 0.5-2 h, and the pH value corresponding to acidity is adjusted to between 2.0 and 3.0.
[0040] Specifically, in one embodiment of the present invention, the silicon source may be ethyl orthosilicate, and the organosilane modifier includes methyltrioxymethylsilane, vinyltrioxyethylsilane, dimethyldiethoxysilane, ethynyltrimethoxysilane and octadecyltrimethoxysilane.
[0041] In one embodiment of the present invention, after the activated cyanobacteria powder and the modified silica hydrosol are prepared, the two need to be composited. Specifically, the activated cyanobacteria powder is dispersed in the hydrophobically modified silica hydrosol to obtain the silica hydrogel, including: adding the activated cyanobacteria powder to the silica hydrosol, adding ammonia water after ultrasonic dispersion treatment, adjusting the pH value to alkaline, and obtaining the silica hydrogel.
[0042] In this embodiment, during the composite treatment of the activated cyanobacteria powder and the modified silica hydrosol, a certain amount of activated cyanobacteria powder is added to the modified silica hydrosol, and then subjected to ultrasonic dispersion treatment. After the dispersion treatment, a certain amount of ammonia water is added to the dispersed system, and the pH value of the system is adjusted to alkaline, for example, between 9.0 and 10.0, to obtain the silica hydrogel.
[0043] Preferably, the mass volume ratio of the activated cyanobacteria powder and the silica hydrosol is 1:(20-80), the ultrasonic decomposition time is 15-30 min, the concentration of ammonia water is 0.5 mol / L, and the pH value corresponding to alkalinity is adjusted to between 9.0 and 10.0.
[0044] In one embodiment of the present invention, the silica hydrogel is subjected to aging and freeze-drying treatments in sequence to obtain a silica aerogel composite material containing cyanobacteria, including: aging the silica hydrogel to obtain a silica wet gel; soaking and washing the silica wet gel in water at room temperature until it becomes neutral; placing the neutral silica wet gel in a silica gel mold and freeze-drying to obtain a silica aerogel composite material containing cyanobacteria. In this embodiment, when the silica hydrogel is aged, the aging time can be set at 12h~36h, and the aging temperature can be set at 30℃~60℃ to ensure the aging effect. Before the freeze-drying treatment, the silica wet gel is soaked and washed in water at room temperature to make the silica wet gel neutral. After the silica wet gel is neutral, it is further added to a silica gel mold for freeze-drying to obtain a silica aerogel composite material containing cyanobacteria. Finally, the cyanobacteria-silica aerogel composite material is subjected to high-temperature carbonization treatment to obtain a carbon / silica aerogel block material, which can make the carbon / silica aerogel block material have the advantages of two materials, namely, the natural fiber structure of cyanobacteria is combined with silica particles. After carbonization, the mechanical strength of the silica aerogel can be improved, and the thermal stability of the silica aerogel can be improved.
[0045] Preferably, during the aging treatment, the aging time is 12h~36h, and the aging temperature is 30℃~60℃; during the low-temperature freezing process, the freezing temperature is less than -40℃, and the freezing time is 24h~36h; the vacuum drying pressure is less than 5Pa.
[0046] In one embodiment of the present invention, in step S30, the high temperature carbonization process may include: Step S301: Raise the temperature from room temperature to 350°C.
[0047] Step S302: Maintain the temperature at 350°C for 3 hours.
[0048] Step S303: Raise the temperature from 350°C to 600°C~800°C.
[0049] Step S304: Maintain the temperature at 600°C-800°C for 4 hours.
[0050] In this embodiment, during the high-temperature carbonization process, the temperature treatment process is a process of increasing in stages.
[0051] Preferably, the heating rate from room temperature to 350°C and from 350°C to 600°C-800°C is 2°C / min.
[0052] Embodiment 1 In a preferred embodiment of the present invention, a method for preparing an aerogel block material is provided, and the specific steps are as follows: Step 1: Preparation of activated cyanobacteria powder: 1.5 g of cyanobacteria powder was dispersed in 250 mL of potassium hydroxide solution with a concentration of 20 wt%, and the solution was placed in an oscillator and oscillated at room temperature for 12 hours. After activation, the sample was centrifuged and washed to neutrality. The obtained sample was placed in a 100°C oven for vacuum drying to finally obtain the activated cyanobacteria powder.
[0053] Step 2: Preparation of silica hydrosol: 1.0 mL of tetraethyl orthosilicate was added to a mixture of 20 mL of ethanol and 20 mL of water, and the mixture was dispersed by mechanical stirring for 5 minutes. Then, 0.5 mL of an organosilane modifier, methyltrioxymethylsilane, was added dropwise thereto, and the mixture was dispersed by mechanical stirring for 20 minutes. A hydrochloric acid solution having a concentration of 0.1 mol / L was added dropwise to the above system, the pH was adjusted to 2.0, and the mixture was hydrolyzed for 20 minutes to obtain a silica hydrosol.
[0054] Step 3: Dispersion, compounding and aging treatment: 1.0 g of activated cyanobacteria powder was added to 25 mL of silica hydrosol, and after ultrasonic dispersion for 20 min, a 0.5 mol / L ammonia solution was added to the system, the pH was adjusted to 10.0, and mechanical stirring was carried out for 20 min. The silica hydrosol was further hydrolyzed and polycondensed, and aged at 35°C for 12 h to obtain a jelly-like cyanobacteria / silica wet gel (silica wet gel containing cyanobacteria). The obtained cyanobacteria / silica wet gel was soaked in deionized water, and the water was changed every 3 h until it was neutral.
[0055] Step 4: Freeze-drying: The cyanobacteria / silica wet gel was placed in a silica gel mold and placed in a freeze dryer for freeze drying at -50°C for 2 days to obtain the cyanobacteria / silica aerogel.
[0056] Step 5: Carbonization to prepare carbon / silicon dioxide aerogel blocks: The cyanobacteria / silica aerogel block was carbonized in a nitrogen atmosphere under the following conditions: the sample was heated from room temperature to 350°C for 3 hours, then heated from 350°C to 700°C for 4 hours, with a heating rate of 2°C min. Finally, a carbon / silica aerogel block was obtained.
[0057] Embodiment 2 In a preferred embodiment of the present invention, a method for preparing an aerogel block material is provided, and the specific steps are as follows: Step 1: Preparation of activated cyanobacteria powder: 1.5 g of cyanobacteria powder was dispersed in 200 mL of sodium hydroxide solution with a concentration of 20 wt%, and the solution was placed in an oscillator and oscillated at room temperature for 12 h. After activation, the sample was centrifuged and washed to neutrality. The obtained sample was placed in a 100 ° C oven for vacuum drying to finally obtain the activated cyanobacteria powder.
[0058] Step 2: Preparation of silica hydrosol: 1.0 mL of tetraethyl orthosilicate was added to a mixture of 10 mL of ethanol and 30 mL of water, and the mixture was dispersed by mechanical stirring for 5 minutes. Then, 1.0 mL of vinyl trioxyethyl silane, an organosilane modifier, was added dropwise thereto, and the mixture was dispersed by mechanical stirring for 20 minutes. A hydrochloric acid solution with a concentration of 0.1 mol / L was added dropwise to the above system, the pH was adjusted to 2.5, and the mixture was hydrolyzed for 20 minutes to obtain a silica hydrosol.
[0059] Step 3: Dispersion, compounding and aging treatment: 1.0 g of activated cyanobacteria powder was added to 30 mL of silica hydrosol, and after ultrasonic dispersion for 20 min, a 0.5 mol / L ammonia solution was added to the system, the pH was adjusted to 10.0, and mechanical stirring was carried out for 20 min. The silica hydrosol was further hydrolyzed and polycondensed, and aged at 60°C for 12 h to obtain a jelly-like cyanobacteria / silica wet gel (silica wet gel containing cyanobacteria). The obtained cyanobacteria / silica wet gel was soaked in deionized water, and the water was changed every 3 h until it was neutral.
[0060] Step 4: Freeze-drying: The cyanobacteria / silica wet gel was placed in a silica gel mold and placed in a freeze dryer for freeze drying at -60°C for 2 days to obtain the cyanobacteria / silica aerogel.
[0061] Step 5: Carbonization to prepare carbon / silicon dioxide aerogel blocks: The cyanobacteria / silica aerogel block was carbonized in a nitrogen atmosphere. The carbonization conditions were as follows: the sample was heated from room temperature to 350°C, kept constant for 3 hours, and then heated from 350°C to 700°C, kept constant for 4 hours, and the heating rate was 2°C / min. Finally, a carbon / silica aerogel block was obtained.
[0062] Embodiment 3 In a preferred embodiment of the present invention, a method for preparing an aerogel block material is provided, and the specific steps are as follows: Step 1: Preparation of activated cyanobacteria powder: 1.5 g of cyanobacteria powder was dispersed in 200 mL of potassium hydroxide solution with a concentration of 30 wt%, and the solution was placed in an oscillator and oscillated at room temperature for 12 h. After activation, the sample was centrifuged and washed to neutrality. The obtained sample was placed in a 100 ° C oven for vacuum drying to finally obtain the activated cyanobacteria powder.
[0063] Step 2: Preparation of silica hydrosol: 1.0 mL of ethyl orthosilicate was added to a mixture of 25 mL of ethanol and 15 mL of water, and the mixture was dispersed by mechanical stirring for 5 minutes. Then, 1.5 mL of dimethyldiethoxysilane, an organosilane modifier, was added dropwise thereto, and the mixture was dispersed by mechanical stirring for 20 minutes. A hydrochloric acid solution with a concentration of 0.1 mol / L was added dropwise to the above system, the pH was adjusted to 2.0, and the silica hydrosol was obtained after a hydrolysis reaction for 20 minutes.
[0064] Step 3: Dispersion, compounding and aging treatment: 1.0 g of activated cyanobacteria powder was added to 20 mL of silica hydrosol, and after ultrasonic dispersion for 20 min, a 0.5 mol / L ammonia solution was added to the system, the pH was adjusted to 9.0, and mechanical stirring was carried out for 20 min. The silica hydrosol was further hydrolyzed and polycondensed, and aged at 40°C for 24 h to obtain a jelly-like cyanobacteria / silica wet gel (silica wet gel containing cyanobacteria). The obtained cyanobacteria / silica wet gel was soaked in deionized water, and the water was changed every 3 h until it was neutral.
[0065] Step 4: Freeze-drying: The cyanobacteria / silica wet gel was placed in a silica gel mold and placed in a freeze dryer for freeze drying at -55°C for 3 days to obtain the cyanobacteria / silica aerogel.
[0066] Step 5: Carbonization to prepare carbon / silicon dioxide aerogel blocks: The cyanobacteria / silica aerogel block was carbonized in a nitrogen atmosphere. The carbonization conditions were as follows: the sample was heated from room temperature to 350°C, kept constant for 3 hours, and then heated from 350°C to 800°C, kept constant for 4 hours, and the heating rate was 2°C / min. Finally, a carbon / silica aerogel block was obtained.
[0067] Embodiment 4 In a preferred embodiment of the present invention, a method for preparing an aerogel block material is provided, and the specific steps are as follows: Step 1: Preparation of activated cyanobacteria powder: 1.5 g of cyanobacteria powder was dispersed in 200 mL of potassium hydroxide solution with a concentration of 30 wt%, and the solution was placed in an oscillator and oscillated at room temperature for 12 h. After activation, the sample was centrifuged and washed to neutrality. The obtained sample was placed in a 100 ° C oven for vacuum drying to finally obtain the activated cyanobacteria powder.
[0068] Step 2: Preparation of silica hydrosol: 1.0 mL of ethyl orthosilicate was added to a mixture of 30 mL of ethanol and 10 mL of water, and the mixture was dispersed by mechanical stirring for 5 minutes. Then, 2.0 mL of an organosilane modifier, ethynyltrimethoxysilane, was added dropwise thereto, and the mixture was dispersed by mechanical stirring for 20 minutes. A hydrochloric acid solution having a concentration of 0.1 mol / L was added dropwise to the above system, the pH was adjusted to 3.0, and the silica hydrosol was obtained after a hydrolysis reaction for 20 minutes.
[0069] Step 3: Dispersion, compounding and aging treatment: 1.5 g of activated cyanobacteria powder was added to 35 mL of silica hydrosol, and after ultrasonic dispersion for 40 min, a 0.5 mol / L ammonia solution was added to the system, the pH was adjusted to 9.5, and mechanical stirring was carried out for 30 min. The silica hydrosol was further hydrolyzed and polycondensed, and aged at 50°C for 2 d to obtain a jelly-like cyanobacteria / silica wet gel (silica wet gel containing cyanobacteria). The obtained cyanobacteria / silica wet gel was soaked in deionized water, and the water was changed every 3 h until it was neutral.
[0070] Step 4: Freeze-drying: The cyanobacteria / silica wet gel was placed in a silica gel mold and placed in a freeze dryer for freeze drying at -60°C for 3 days to obtain the cyanobacteria / silica aerogel.
[0071] Step 5: Carbonization to prepare carbon / silicon dioxide aerogel blocks: The cyanobacteria / silica aerogel block was carbonized in a nitrogen atmosphere under the following conditions: the sample was heated from room temperature to 350°C, kept at this temperature for 3 hours, and then heated from 350°C to 650°C, kept at this temperature for 4 hours, with a heating rate of 2°C / min. Finally, a carbon / silica aerogel block was obtained.
[0072] Embodiment 5 In a preferred embodiment of the present invention, a method for preparing an aerogel block material is provided, and the specific steps are as follows: Step 1: Preparation of activated cyanobacteria powder: 1.0 g of cyanobacteria powder was dispersed in 200 mL of sodium hydroxide solution with a concentration of 30 wt%, and the solution was placed in an oscillator and oscillated at room temperature for 12 h. After activation, the sample was centrifuged and washed to neutrality. The obtained sample was placed in a 100 ° C oven for vacuum drying to finally obtain the activated cyanobacteria powder.
[0073] Step 2: Preparation of silica hydrosol: 1.0 mL of ethyl orthosilicate was added to a mixture of 30 mL of ethanol and 10 mL of water, and the mixture was dispersed by mechanical stirring for 5 minutes. Then, 1.0 mL of an organosilane modifier octadecyltrimethoxysilane was added dropwise thereto, and the mixture was dispersed by mechanical stirring for 20 minutes. A hydrochloric acid solution with a concentration of 0.1 mol / L was added dropwise to the above system, the pH was adjusted to 2.0, and the mixture was hydrolyzed for 20 minutes to obtain a silica hydrosol.
[0074] Step 3: Dispersion, compounding and aging treatment: 1.0 g of activated cyanobacteria powder was added to 30 mL of silica hydrosol, and after ultrasonic dispersion for 30 min, a 0.5 mol / L ammonia solution was added to the system, the pH was adjusted to 10.0, and mechanical stirring was carried out for 30 min. The silica hydrosol was further hydrolyzed and polycondensed, and aged at 45°C for 1 day to obtain a jelly-like cyanobacteria / silica wet gel (silica wet gel containing cyanobacteria). The obtained cyanobacteria / silica wet gel was soaked in deionized water, and the water was changed every 3 hours until it was neutral.
[0075] Step 4: Freeze-drying: The cyanobacteria / silica wet gel was placed in a silica gel mold and placed in a freeze dryer for freeze drying at -50°C for 2 days to obtain the cyanobacteria / silica aerogel.
[0076] Step 5: Carbonization to prepare carbon / silicon dioxide aerogel blocks: The cyanobacteria / silica aerogel block was carbonized in a nitrogen atmosphere. The carbonization conditions were as follows: the sample was heated from room temperature to 350°C, kept constant for 3 hours, and then heated from 350°C to 800°C, kept constant for 4 hours, and the heating rate was 2°C / min. Finally, a carbon / silica aerogel block was obtained.
[0077] Comparative Example Preparation of Pure Silica Aerogel 1.0 mL of tetraethyl orthosilicate was added to a mixture of 20 mL of ethanol and 20 mL of water. After mechanical stirring and dispersion for 5 min, 0.5 mL of organosilane modifier methyltrioxymethylsilane was added dropwise, and mechanical stirring and dispersion were performed for 20 min. A hydrochloric acid solution with a concentration of 0.1 mol / L was added dropwise to the above system, and the pH was adjusted to 2.0. After hydrolysis reaction for 20 min, a silica hydrosol was obtained. A 0.5 mol / L ammonia solution was added to the system, and the pH was adjusted to 10.0. Mechanical stirring was performed for 20 min. The silica hydrosol was further hydrolyzed and polycondensed, and aged at 35 ° C for 12 h to obtain a silica wet gel. The obtained silica wet gel was soaked in deionized water, and the water was changed every 3 h until it was neutral. Finally, the above silica wet gel was placed in a silica gel mold and placed in a freeze dryer for freeze drying. The freeze drying conditions were -50 ° C and freeze drying for 2 days to obtain silica aerogel.
[0078] The present invention also provides an aerogel prepared by the above-mentioned preparation method.
[0079] See also Figure 1, which is a macroscopic optical image of the carbon / silicon dioxide aerogel structure performance obtained in the above Example 1 when tested and analyzed. In the obtained carbon / silicon dioxide aerogel block, it can be seen that the aerogel has a good structure after drying and carbonization, and still maintains a block structure without breaking or collapsing, indicating that its structure is relatively stable and has a certain mechanical strength.
[0080] See also Figure 2 , is a microscopic morphology of the carbon / silicon dioxide aerogel obtained in the above Example 1 when undergoing testing and analysis. Under SEM (scanning electron microscope), it can be seen that the carbonized fibrous structured cyanobacteria and silicon dioxide are effectively compounded.
[0081] See also Figure 3 , is the XRD (X-ray diffraction analysis) diagram of the sample when the carbon / silicon dioxide aerogel structure obtained in the above-mentioned Examples 1 to 5 is tested and analyzed. Among them, a, b, c, d, and e correspond to the samples in Examples 1 to 5 respectively. Figure 3 It can be seen that all carbon / silica aerogels have a broad diffraction peak between =18-30°, which is formed by the superposition of amorphous silica and carbon, indicating that the carbon / silica aerogel has an amorphous structure.
[0082] See also Figure 4 , which is a performance parameter table of carbon / silica aerogel obtained when the structural performance of the carbon / silica aerogel obtained in the above-mentioned Examples 1 to 5 is tested and analyzed. It can be seen from the table that all carbon / silica aerogel surfaces are hydrophobic, the volume density is relatively small in the range of 29-37 mg / cm³, and at the same time, they have a high specific surface area, indicating the presence of a rich pore structure, and at the same time, they have a low thermal conductivity, and the minimum thermal conductivity is 0.1055 W / mk, which is mainly to examine the thermal insulation performance of carbon / silica aerogel blocks.
[0083] See also Figure 5 , which is a comparison diagram of the mechanical properties of the carbon / silica aerogel and the silica aerogel obtained in the above Example 1 and the comparative example. It can be seen from the figure that the stress of the carbon / silica aerogel in Example 1 is much greater than the stress of the pure silica aerogel, indicating that the mechanical properties of the cyanobacteria-based carbon / silica aerogel have been significantly improved.
[0084] See also Figure 6 , is the infrared thermal imaging structure of the carbon / silicon dioxide aerogel obtained in the above Example 1 when the performance is tested and analyzed. It can be seen that after the aerogel is heated from room temperature to 87°C for nearly 19 minutes, its surface can still be maintained at about 40°C, indicating that the material has good thermal insulation performance.
[0085] In summary, the present invention discloses a method for preparing an aerogel block material and an aerogel prepared therefrom. The activated cyanobacteria powder is dispersed in a hydrophobically modified silica sol by an ultrasonic dispersion method. Since cyanobacteria contain a large amount of protein, amino acid and polysaccharide, and due to the presence of amino, hydroxyl and carboxyl active groups in its molecules, the compatibility between cyanobacteria and silica sol can be improved, and the interaction between cyanobacteria powder as a carbon precursor and silica colloidal particles can be improved. Moreover, by activating the cyanobacteria powder, the specific surface area of the cyanobacteria-based carbon material can be effectively increased, so that the cyanobacteria-based carbon material has a rich porous structure. Further, through aging, freeze-drying and carbonization processes, a carbon / silica aerogel block material is finally obtained. The fibrous structure of cyanobacteria can be used to effectively improve the mechanical strength of the silica aerogel after carbonization, and at the same time improve the thermal stability of the silica aerogel under high temperature conditions. Therefore, the present invention effectively overcomes the various shortcomings of the prior art and has a high industrial utilization value.
[0086] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing an aerogel block material, characterized in that: The steps include: dispersing the activated cyanobacteria powder into the hydrophobically modified silica hydrosol to obtain the silica hydrogel; The silica hydrogel is subjected to aging, washing and freeze-drying treatments in sequence to obtain a silica aerogel composite material containing cyanobacteria; The cyanobacteria-containing silica aerogel composite material is carbonized at high temperature in an inert gas using the cyanobacteria as a carbon precursor to obtain a carbon / silicon dioxide aerogel block material.
2. The method for preparing an aerogel block material according to claim 1, characterized in that: Before dispersing the activated cyanobacteria powder into the hydrophobically modified silica hydrosol to obtain the silica hydrogel, the method comprises: Add the blue algae powder to the activator solution, place it in an oscillator, and oscillate at room temperature for activation; After the activation is completed, centrifugation is performed and the mixture is washed until neutral, and then placed in a 100° C. oven for vacuum drying to obtain the activated cyanobacteria powder.
3. The method for preparing an aerogel block material according to claim 2, characterized in that: The activator solution comprises an activator and water, the concentration of the activator solution is 10wt% to 30wt%, and the mass ratio of the cyanobacteria powder to the activator in the activator solution is 1:(1 to 5).
4. The method for preparing an aerogel block material according to claim 1, characterized in that: Before dispersing the activated cyanobacteria powder into the silica sol modified by the organosilane modifier, the method further comprises: Adding a silicon source and an organosilane modifier to a mixed solution of ethanol and water at room temperature for mixing; After the mixing, hydrochloric acid is added to adjust the pH value to acidic, and after a period of hydrolysis reaction, the silicon dioxide hydrosol is obtained.
5. The method for preparing an aerogel block material according to claim 4, characterized in that: The mass ratio of the silicon source to the organosilane modifier is 1:(0.5-7), the volume ratio of the ethanol to water is 1:(0.5-3), the concentration of hydrochloric acid is 0.1 mol / L, the hydrolysis reaction time is 0.5-2h, and the pH value corresponding to the acidity is adjusted to between 2.0 and 3.
0.
6. The method for preparing an aerogel block material according to claim 1, characterized in that: The activated cyanobacteria powder is dispersed in a hydrophobically modified silica hydrosol to obtain a silica hydrogel, comprising: The activated cyanobacteria powder is added to the silica hydrosol, and after ultrasonic dispersion treatment, ammonia water is added to adjust the pH value to alkaline to obtain the silica hydrogel.
7. The method for preparing an aerogel block material according to claim 6, characterized in that: The mass volume ratio of the activated cyanobacteria powder to the silicon dioxide hydrosol is 1:(20-80), the ultrasonic decomposition time is 15-30 minutes, the concentration of ammonia water is 0.5 mol / L, and the pH value corresponding to alkalinity is adjusted to between 9.0 and 10.
0.
8. The method for preparing an aerogel block material according to claim 1, characterized in that: The silica hydrogel is subjected to aging, washing and freeze-drying treatments in sequence to obtain a cyanobacteria-containing silica aerogel composite material, comprising: Performing an aging treatment on the silica hydrogel to obtain a silica wet gel; The wet silica gel is placed in water at room temperature and soaked and washed until it becomes neutral; The neutral silicon dioxide wet gel is placed in a silica gel mold for freeze drying, low temperature freezing, and vacuum drying to obtain the silicon dioxide aerogel composite material containing cyanobacteria.
9. The method for preparing an aerogel block material according to claim 8, characterized in that: During the aging treatment, the aging time is 12h to 36h, and the aging temperature is 30°C to 60°C; During the low-temperature freezing process, the freezing temperature is less than -50°C and the freezing time is 24h to 36h; The pressure of the vacuum drying is less than 5 Pa; The high temperature carbonization process comprises: Heating from room temperature to 350°C; Keep at 350℃ for 3h; Heating from 350℃ to 600℃~800℃; Keep the temperature at 600℃~800℃ for 4h; The heating rates from room temperature to 350°C and from 350°C to 600°C to 800°C are 2°C / min.
10. An aerogel prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
One-dimensional and two-dimensional biochar synergistically enhanced carbon aerogel material as well as preparation method and application thereof
CN114380285A